2019
DOI: 10.1002/qj.3612
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dynamical downscaling of general circulation models using continuous data assimilation

Abstract: Continuous data assimilation (CDA) is successfully implemented for the first time for efficient dynamical downscaling of a global atmospheric reanalysis. A comparison of the performance of CDA with the standard grid and spectral nudging techniques for representing long‐ and short‐scale features in the downscaled fields using the Weather Research and Forecast (WRF) model is further presented and analysed. The WRF model is configured at 0.25° × 0.25° horizontal resolution and is driven by 2.5° × 2.5° initial and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…we have further recently introduced and successfully tested a new dynamical downscaling algorithm with WRF, based on the Continuous Data Assimilation approach (Desamsetti et al 2019). Downscaling ensembles from the global operational centers remain computationally demanding in terms of both computational cost and storage.…”
Section: Ireds Developmentsmentioning
confidence: 99%
“…we have further recently introduced and successfully tested a new dynamical downscaling algorithm with WRF, based on the Continuous Data Assimilation approach (Desamsetti et al 2019). Downscaling ensembles from the global operational centers remain computationally demanding in terms of both computational cost and storage.…”
Section: Ireds Developmentsmentioning
confidence: 99%
“…Long-time accuracy of Algorithm 3.1. We now consider the difference between the solutions of (13) - (15) to the NSE solution. We will show that the algorithm solution converges to the true solution, up to an optimal O(∆t + h k+1 ) discretization error, independent of the initial condition, provided a restriction on the coarse mesh width and nudging parameters.…”
Section: 2mentioning
confidence: 99%
“…This stimulated a large amount of recent research on the CDA algorithm; see, e.g., [3,6,7,10,11,13,17,18,19,20,21,22,27,31,30,35,40,41] and the references therein. The recent paper [15] showed that CDA can be effectively used for weather prediction, showing that it can indeed be a powerful tool on practical large scale problems. Convergence of discretizations of CDA models was studied in [30,41,27,21] , and found results similar to those at the continuous level.…”
mentioning
confidence: 99%
“…However, at high frequencies in-situ floating measurements have to be treated carefully since error profiles may show relevant peaks when the buoy resonance falls close to the driving metocean forcings. Model conditioning, based on assimilating RS/in-situ data as a Bayesian (conditional) estimation problem (Desamsetti et al, 2019), benefits from considering spatially distributed observations (for spatial structure) and high resolution time series (for temporal structure). The assimilation should consider bulk variables (e.g., significant wave height) and physically key properties, such as spectral tails, because well reproduced tails indicate a physically correct balance between generation and dissipation, adding reliability to the conditioning.…”
Section: Evolution Of Coastal Data Conditioningmentioning
confidence: 99%